Quem é o melhor dj do mundo? disputas simbólicas na cena de música eletrônica - Pinto, Marcelo Garson Braule (2010)
The purpose of this dissertation is to set forth the centrality of the discussions on taste in musical scene, particularly in the electronic music scene. We have, therefore, selected a specific case, namely the election of the best dj of the year by DJ, an English electronic music magazine. This event called the attention of those beyond the boundaries of the electronic scene when Dj Tiesto was awarded the first place for three times in a row. As a consequence he was labeled as a Dj Superstar and the best Dj in the world . This consecration was seen by the earliest members of the electronic scene as meaning its excessive and deleterious popularization. Our purpose is to point out the ways that opinion is both supported and challenged in the discussion forum in rraur l, one of the Brazilian largest and earliest sites of electronic music. To understand the way by which diverse labels clash is to highlight the power they have to mold reality. We shall see how a culture, initially adopting mechanisms of production, circulation and consumption as a mean to keep its growth under control of a few people, had more recently to deal with values of a corporative culture as a consequence of its growth, marketing and visibility. Supported mostly on Pierre Bourdieu s work on taste and symbolic conflict, our effort is to show that the discourse is the way through which certain members defend their, say, territory while so many others try to insert themselves therein.